1982
DOI: 10.1063/1.331098
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between n-type amorphous hydrogenated silicon films and metal electrodes

Abstract: Articles you may be interested inDrain current reduction by source electrode overlap in hydrogenated amorphous silicon thinfilm transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…These two effects – a drastic loss in series resistance and passivation quality at the same time – can be explained by interdiffusion effects at the amorphous silicon/aluminum interface. Already at temperatures as low as 150 °C aluminum and amorphous silicon will start to form an alloy that greatly improves contact resistivity . Further annealing leads to an extended diffusion of aluminum into the amorphous silicon layers, eventually reaching the interface between the intrinsic passivation layer and the crystalline absorber.…”
Section: Solar Cell Illuminated J–v Parametersmentioning
confidence: 99%
“…These two effects – a drastic loss in series resistance and passivation quality at the same time – can be explained by interdiffusion effects at the amorphous silicon/aluminum interface. Already at temperatures as low as 150 °C aluminum and amorphous silicon will start to form an alloy that greatly improves contact resistivity . Further annealing leads to an extended diffusion of aluminum into the amorphous silicon layers, eventually reaching the interface between the intrinsic passivation layer and the crystalline absorber.…”
Section: Solar Cell Illuminated J–v Parametersmentioning
confidence: 99%
“…2 However, for the case of Al/a-Si:H, the interaction temperature is much lower, starting at about 170°C. 3 It should be noted here that a temperature of about 650°C is required for the solid phase crystallization of a-Si into c-Si. 4 Crystallization of a-Si:H in contact with different contact metals during annealing at relatively low temperatures has been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Ishihara et al reported the presence of pits in the amorphous silicon layers produced by the interdiffusion of both aluminium and amorphous silicon at temperatures as low as 170 °C. 21) Haque et al studied extensively the aluminium-induced crystallisation of amorphous silicon layers and the subsequent changes in their electrical properties at temperatures ranging from 150 to 300 °C. 22,23) Hentzell et al proved the existence of an Al silicide, starting to form at a temperature of approximately 170 °C, prior to the silicon crystallisation.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of aluminium and amorphous silicon layers after annealing at different temperatures has been studied thoroughly by many researchers.Ishihara et al reported the presence of pits in the amorphous silicon layers produced by the interdiffusion of both aluminium and amorphous silicon at temperatures as low as 170°C 21…”
mentioning
confidence: 99%